Comparative analysis of various multilevel inverter symmetrical topologies with minimum number of components - Qasim Hussein Algburi, Ali; V. Ramana Rao, P (International Journal of Engineering and Technology, 2018)
Multilevel inverters (MLI) are frequently used in different fields like, oil and gas sectors, installations of power supply, high power and medium voltage applications and in FACTS (flexible AC transmission system) devices to improve power quality. Lot of topologies has been developed in the literature regarding multilevel inverters such as diode clamped type, flying capacitor type and cascaded H-bridge type multilevel inverters. However, several challenges are being faced while implementing these topologies like more number of switches, more losses and cost. The optimized construction of multilevel inverter is to get more number of levels with less number of switches and low total harmonic distortion. In this paper, three different existing multilevel inverter topologies have been considered and analyzed for five level output voltage. A comparison table is given for number of switches, extra diodes and voltage sources. The total work is carried by using Matlab/simulink software and results are presented.